Non-invasive fetal therapy - Sosa Olavarría, Alberto (2016)
Fetal pharmacologic therapy can be defined as any prenatal treatment administered to the mother with the primary indication of improving perinatal or long-term outcomes for the fetus and the newborn. This review provides an update on the pharmacological therapies for the fetus with anomalies. Fetal anomalies targeted with prenatal pharmacotherapy are a heterogeneous group of structural, endocrine, and metabolic conditions, including brain and spine anomaly, hyaline membrane disease prevention, congenital cystic adenomatoid malformation (CCAM), congenital adrenal hyperplasia, congenital heart block, fetal tachyarrhythmia, inborn errors of metabolism, fetal thyroid disorders, and polyhydramnios. To date, most of the pharmacotherapy for fetal anomalies has been evaluated only in retrospective, uncontrolled studies. Future evaluation will be determined on evidence-based approach to prenatal pharmacological interventions.